BIOSTRATIGRAPHY, MICROFACIES AND DEPOSITIONAL ENVIRONMENTS OF UPPER VISÉAN LIMESTONES FROM THE BURREN REGION, COUNTY CLARE, IRELAND - Gallagher S.J.; MacDermot C.V.; Pracht M.; Sleeman A.G.; Somerville I.D. (My University, 2006)
The Burren region in western Ireland contains an almost continuous record of Viséan (Middle Mississippian) carbonate deposition extending from Chadian to Brigantian times, represented by three formations: the Chadian to Holkerian Tubber Formation, the Asbian Burren Formation and the Brigantian Slievenaglasha Formation. The upper Viséan (Holkerian-Brigantian) platform carbonate succession of the Burren can be subdivided into six distinct depositional units outlined below. (1) An Holkerian to lower Asbian unit of skeletal peloidal and bryozoan bedded limestone. (2) Lower Asbian unit of massive light grey Koninckopora-rich limestone, representing a shallower marine facies. (3) Upper Asbian terraced limestone unit with minor shallowing-upward cycles of poorly bedded Kamaenella-rich limestone with shell bands and palaeokarst features. This unit is very similar to other cyclic sequences of late Asbian age in southern Ireland and western Europe, suggesting a glacio-eustatic origin for this fourth-order cyclicity. (4) Lower Brigantian unit with cyclic alternations of crinoidal/bryozoan limestone and peloidal limestone with coral thickets. These cycles lack evidence of subaerial exposure. (5) Lower Brigantian bedded cherty dark grey limestone unit, deposited during the maximum transgressive phase of the Brigantian. (6) Lower to upper Brigantian unit mostly comprising cyclic bryozoan/crinoidal cherty limestone. In most areas this youngest unit is truncated and unconformably overlain by Serpukhovian sificiclastic rocks. Deepening enhanced by platform-wide subsidence strongly influenced later Brigantian cycle development in Ireland, but localized rapid shallowing led to emergence at the end of the Brigantian. A Cf5 Zone (Holkerian) assemblage of microfossils is recorded from the Tubber Formation at Black Head, but in the Ballard Bridge section the top of the formation has Cf6 Zone (Asbian) foraminiferans. A typical upper Asbian Rugose Coral Assemblage G near the top of the Burren Formation is replaced by a lower Brigantian Rugose Coral Assemblage H in the Slievenaglasha Formation. A similar change in the foraminifetans and calcareous algae at this Asbian-Brigantian formation boundary is recognized by the presence of upper Asbian Cf6√ Subzone taxa in the Burren Formation including Cribrostomum lecomptei, Koskinobigenerina sp., Bradyina rotula and Howchinia bradyana, and in the Slievenaglasha Formation abundant Asteroarchaediscus spp., Neoarchaediscus spp. and Fasciella crustosa of the Brigantian Cf6δ Subzone. The uppermost beds of the Slievenaglasha Formation contain a rare and unusual foraminiferal assemblage containing evolved archaediscids close to tenuis stage indicating a late Brigantian age. Copyright © 2006 John Wiley & Sons, Ltd.
Keywords: BIOSTRATIGRAPHY; CALCAREOUS ALGAE; FORAMINIFERANS; IRELAND; MISSISSIPPIAN; PLATFORM CARBONATES; RUGOSE CORALS; UPPER VISÉAN; Paleozoic::Carboniferous::Mississippian::Middle::Visean; алеозой::Каменноугольная::Средний::Визейский